2022
DOI: 10.3389/fneur.2022.1013083
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke: From pathological mechanisms to neuroprotective strategies

Abstract: Ischemic stroke (IS) has complex pathological mechanisms, and is extremely difficult to treat. At present, the treatment of IS is mainly based on intravenous thrombolysis and mechanical thrombectomy, but they are limited by a strict time window. In addition, after intravenous thrombolysis or mechanical thrombectomy, damaged neurons often fail to make ideal improvements due to microcirculation disorders. Therefore, finding suitable pathways and targets from the pathological mechanism is crucial for the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 197 publications
0
12
0
Order By: Relevance
“…By contrast, the underweight cohort did not have increased values of LDL-C and TG and only had a statistically significantly increased HDL-C compared to the normal weight cohort. The sarcopenia risk for stroke-associated infections is associated with a larger BMI category of ≥ 18.5; thus, we hypothesize that the pathophysiological mechanisms of ischemic stroke are different for our cohorts with larger BMIs 15,16,38 . In addition, it is a well-known fact that a larger body fat distribution, as indicated by an elevated BMI, has a close relationship with the occurrence of metabolic disorders 39 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…By contrast, the underweight cohort did not have increased values of LDL-C and TG and only had a statistically significantly increased HDL-C compared to the normal weight cohort. The sarcopenia risk for stroke-associated infections is associated with a larger BMI category of ≥ 18.5; thus, we hypothesize that the pathophysiological mechanisms of ischemic stroke are different for our cohorts with larger BMIs 15,16,38 . In addition, it is a well-known fact that a larger body fat distribution, as indicated by an elevated BMI, has a close relationship with the occurrence of metabolic disorders 39 .…”
Section: Discussionmentioning
confidence: 87%
“…The findings of yet another study supported this meta-analysis, revealing that the BMI categories of overweight and obesity were associated with an increased risk only in men 5. It has been shown that there is a positive correlation between the whole range of BMI categories and ischemic stroke 6 , with no evidence of a threshold or a J-shaped curve 7,8 . Conversely, the BMI category of underweight in both sexes is also associated with a higher risk of ischemic stroke, and this category has a significantly higher rate of poor short and long-term outcomes than the BMI category of normal weight 9,10,11 . Other studies regarding the association between BMI and the prognosis after acute ischemic stroke have shown that BMI has a non-linear association with 3-month outcomes in men with acute ischemic stroke 8 , and that the BMI categories of underweight and obesity were generally associated with poorer outcomes 12,13,14 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is speculated that the mechanism may be similar to the role of inflammatory cells in acute ischemic stroke. Previous studies have confirmed that when the brain tissue is under hypoxic‐ischemic conditions, the circulating leukocytes may be activated, and the blood‐brain barrier may be impaired, thus aggravating neuronal damage 34–37 . Meanwhile, the inflammatory mediators may be released into the blood, triggering a series of inflammatory reactions 38 .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have confirmed that when the brain tissue is under hypoxic-ischemic conditions, the circulating leukocytes may be activated, and the blood-brain barrier may be impaired, thus aggravating neuronal damage. [34][35][36][37] Meanwhile, the inflammatory mediators may be released into the blood, triggering a series of inflammatory reactions. 38 In addition, it has been suggested that cerebral ischemia may decrease the number of circulating immune cells by activating the sympathetic nervous system and the hypothalamicpituitary-adrenal axis, resulting in a state of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%